Diversity of interstitial nemerteans of the genus Ototyphlonemertes (Nemertea: Monostilifera: Ototyphlonemertidae) in the South China Sea, with a comment on the distribution pattern of the genus - Liu, Hai-Long; Kajihara, Hiroshi; Sun, Shi-Chun (Frontiers in Marine Science, 2022)
The genus Ototyphlonemertes Diesing, 1863, consisting of 33 named species and numerous unnamed morphospecies/molecular entities, is a unique group of nemerteans that possess cerebral statocysts and specifically live in coarse-grained sands. Only eight named species of this genus have yet been recorded from the Indo-Polynesian biogeographic province, which harbors the highest marine biodiversity in the world. In recent years, Ototyphlonemertes were collected from eight sites along the South China Sea coasts. Nine species/entities were revealed by four phylogenetic markers (COI, 16S, 18S, 28S) analyzed by three species delimitation methods: Automatic Barcode Gap Discovery (ABGD), Poisson Tree Process (PTP), and Generalized Mixed Yule Coalescent model (GMYC). Six entities are described as new species based on integration of morphological and molecular species delimitations: Ototyphlonemertes conicobasis sp. nov., Ototyphlonemertes coralli sp. nov., Ototyphlonemertes similis sp. nov., Ototyphlonemertes sinica sp. nov., Ototyphlonemertes subrubra sp. nov., and Ototyphlonemertes yingge sp. nov. No morphological differences were detected between two entities and Ototyphlonemertes chernyshevi Kajihara et al., 2018, despite large genetic differences, so are treated as candidate species. Ototyphlonemertes ani Chernyshev, 2007 is first recorded in China. Based mostly on results of phylogenetic analyses, two previously established subgenera are re-defined, and a new subgenus, Procso subgen. nov., is established. Through reviewing the existing studies, we recognize 101 species/entities of Ototyphlonemertes, which are distributed in 18 marine biogeographic provinces. Most (88.1%) of them are endemic to a single biogeographic province, and evolutionary lineages endemic to a geographic area are not uncommon. Maximum diversity has been recorded in the Indo-Polynesian Province (22 species), though sampling to date has covered only a small part of the biogeographic province.